PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT TIRTA INVESTAMA (AQUA) SUBANG PADA EKONOMI MASYARAKAT LOKAL DI DESA DARMAGA - Tititn kartini; Moch Gilang Gustian (Fakultas Ilmu Administrasi Universitas Subang, 2022)
Abstrak Penelitian ini bertujuan untuk mengetahui optimalisasi penerapan Corporate Social Responsibility (CSR) PT Tirta Investama (AQUA) Subang pada ekonomi masyarakat lokal di Desa Darmaga. Penelitian ini dilakukan melalui pendekatan kualitatif. Sumber data primer dan sekunder diperoleh dari informan yang ditentukan melalui purvosive sampling dan snowball dengan teknik pengumpulan data menggunakan observasi, wawancara, dan kajian dokumen. Adapun teknik analisis data menggunakan model Miles and Huberman, meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukan bahwa Penerapan CSR AQUA Subang pada ekonomi masyarakat lokal di Desa Darmaga sudah optimal karena memerhatikan dan termasuk ke dalam kategori dimensi CSR yaitu Corporate Social Marketing, Corporate Philantrophy, dan Social Responsible Business Practice (Community Development) dengan didasari oleh faktor kesadaran perusahaan akan tanggung jawab sosialnya, yang pelaksanannya menggunakan model keterlibatan langsung perusahaan dan bermitra dengan lembaga serta melalui tahapan perencanaan, implementasi, dan evaluasi serta pelaporan. Penerapan CSR AQUA Subang pada ekonomi masyarakat lokal di Desa Darmaga menunjang pembangunan berkelanjutan (sustainable development), dan berkontribusi mengatasi masalah ekonomi, yaitu: kemiskinan, pengangguran, dan minimnya pelaku usaha, serta berdampak positif secara langsung maupun tidak langsung. Kata kunci: CSR, AQUA Subang, Ekonomi, Desa Darmaga. Abstrack This study aims to determine the optimization of the implementation of Corporate Social Responsibility (CSR) of PT Tirta Investama (AQUA) Subang on the economy of the local community in Darmaga Village. This study discusses corporate social responsibility in the economic field of local communities with a case study at PT. Tirta Investama (AQUA) Subang in Darmaga Village. This research was conducted using a qualitative approach. Primary and secondary data sources were obtained from informants who were determined through purvosive sampling and snowball with data collection techniques using observation, interviews, and document review. The data analysis technique uses the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The implementation of PT Tirta Investama (AQUA) Subang's Corporate Social Responsibility (CSR) in the Local Community Economy in Darmaga Village called the Economic Development Program (ECODEV) in 2021, namely: the establishment of the Mandiri Jaya Cooperative in Darmaga Village, Monthly Assistance for Management and Members, Mandiri Jaya Abadi Cooperative, Cooperative Financial Application Assistance, Marketing Assistance and Packaging of MSME Products with the MSME Office and Central, Advocacy for MSME Legality in the form of I-SMEs, Halal MUI, PIRT, Basic training workshops and coffee business-Basic Manual Brew (Coffee Damping Class) , Proximity and Arjuna Maribaya Cibodas Coffee Business Visits, and Asset Inventory and Voluntary Donations and Assistance. The results show that the implementation of AQUA Subang's CSR in the local community economy in Darmaga Village is optimal because it pays attention to and is included in the category of CSR dimensions, namely Corporate Social Marketing, Corporate Philanthropy, and Social Responsible Business Practice (Community Development) based on the company's awareness factor about its social responsibility, which is implemented using a direct involvement model of the company and in partnership with institutions as well as through the stages of planning, implementation, and evaluation and reporting. The implementation of AQUA Subang's CSR in the local community's economy in Darmaga Village supports sustainable development and contributes to overcoming economic problems, namely: poverty, unemployment, and the lack of business actors, as well as having a positive direct or indirect impact. Keywords: CSR, Subang AQUA, Economy, Darmaga Village